DECISION SUPPORT SYSTEM FOR SELECTION OF ACHIEVEMENT TEACHERS TO GIVE AWARDS AT SMAS IMELDA MEDAN USING THE SAW METHOD - Rajagukguk , Denni M.; Manalu , Mamed Rofendi; Sihombing , Monang Juanda Tua; Panjaitan, Muhammad Iqbal (Sean Institute, 2022)
In general, the implementation of the selection of outstanding teachers has been running smoothly in accordance with predetermined criteria. However, it is felt that the implementation is still not optimal so that improvements need to be made, especially in the assessment aspect. In evaluating the selection of outstanding teachers at SMAS Imelda Medan, there are several assessment criteria namely Obedience, discipline, responsibility, cooperation, assessment of the learning process, teacher activity in schools and honesty. In order for the implementation of the teacher selection to work, this is what makes the need for a decision support system that is able to provide consistency of assessment with the application of normalization and provide convenience in the results of the value to be determined from each test. The decision support system used in this study is to use the Simple Additive Weighting (SAW) method. This method strongly supports the assessment of criteria and weighting of values. The criteria used are based on the results of data analysis and the results of the assessment of each test. This system is also useful for schools in determining and calculating scores in determining teachers who deserve to get awards in the selection of outstanding teachers. The purpose of this research is to develop a system decision support that can facilitate the process selection of outstanding teachers and applying the SAW method in a decision support system to facilitate in determine the ranking of outstanding teachers.